Kerinci Cinnamon Leaf (Cinnamomum burmanii) and Tangkit Pineapple Core (Ananas comosus) Extracts in Mouthwash Formulation: Potential for Preventing Dental Plaque Growth in Special Needs Childre - Fitria, Karin Tika; Handayatun, Naning Nur; Baroroh, Faridah; Pertiwi, Deasy Vanda (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2024)
Dental plaque is a significant factor in developing oral diseases, particularly in children with special needs who may face challenges maintaining oral hygiene. This study explores the potential of a mouthwash formulation incorporating Kerinci cinnamon leaf (Cinnamomum burmanii) and Tangkit pineapple core (Ananas comosus) extracts in preventing dental plaque growth. Both extracts were chosen due to their known antibacterial properties and natural origin, making them suitable for children with sensitivities to synthetic chemicals. The formulation was tested in varying ratios to determine the most effective combination for inhibiting the growth of Streptococcus mutans, a primary bacterium responsible for dental plaque. The results indicated that a 50:50 ratio of cinnamon leaf and pineapple core extracts exhibited the highest antibacterial activity (p-value 0,034), outperforming other ratios such as 75:25 and 25:75. This suggests a synergistic interaction between the two extracts, enhancing their combined efficacy. Further research is recommended to optimize the formulation and evaluate its long-term effectiveness and safety in clinical settings